KULIAH ONLINE DI MASA PANDEMI COVID-19 - Trifena Elen; Rizki Rahmadania Putri (Universitas Prof. Dr. Moestopo (Beragama), 2020)
Education is something essential for human civilization. Formal education is usually carried out at school or university face-to-face. However, due to the COVID-19 worldwide pandemic in 2020, teaching and learning activities at all levels have turned into online classes. University is one education level that is affected by COVID-19. In this journal article, researchers will examine the effectiveness of online lectures during the COVID-19 pandemic. The theory used in this research is Walther's Computer Mediated Communication theory. This theory describes communication through computer media. Researchers will use positivistism paradigm with a qualitative approach and conduct observations, interviews with lecturers and students of the LSPR Institute Communication and Business and also study literature. The results of this study indicate that online lectures during the COVID-19 pandemic are less effective in terms of providing material but are quite acceptable given the limited space for people today. Based on the results of this study, we suggest that the government should further improve the quality of online lectures during the COVID-19 pandemic. The results obtained are also more satisfying.